Penerapan Media Pembelajaran Random Wheels Open the Box dalam Meningkatkan Hasil Belajar Peserta Didik Kelas IV Sekolah Dasar Negeri 178 Tuban Kabupaten Luwu Timur - Pratama, Rendhy; Thaha, Hisban; Efendi, Erwatul (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the application and effectiveness of Random Wheels Open the Box learning media in improving the learning outcomes of students in Islamic Religious Education and Ethics subjects in grade IV of SD Negeri 178 Tuban, East Luwu Regency. This study used Classroom Action Research (CAR) conducted in two cycles, each comprising the stages of planning, implementation of actions, observation, and reflection. The research subjects consisted of 18 fourth-grade students. Data were collected through observation of learning activities, learning outcome tests, and documentation. Data analysis was conducted using quantitative and qualitative descriptive methods. Learning outcome data were analysed by calculating the average score and percentage of learning completeness in each cycle, while student activity data were analysed descriptively based on the observation results for each activity indicator. The results showed an increase in learning outcomes from an average score of 47.78 in the initial test to 66.67 in cycle I and an increase to 88.89 in cycle II with a classical mastery level of 100%. Student learning activities also increased and were in the ‘Very Good’ category for all indicators. Thus, the Random Wheels Open the Box media is effective in improving student learning outcomes and activity.